2002
DOI: 10.1038/sj.onc.1205310
|View full text |Cite
|
Sign up to set email alerts
|

Molecular follow-up of preneoplastic lesions in bronchial epithelium of former Chernobyl clean-up workers

Abstract: Ionizing radiation is a potent lung carcinogen, but the precise molecular damage associated with it is still unknown. In this study we investigated cancer-related molecular abnormalities including K-ras (codon 12) mutation, p16 INK4Apromoter hypermethylation and microsatellite alterations at seven chromosomal regions in successive biopsies obtained from former Chernobyl cleanup workers in comparison with smokers and nonsmokers who have never had radiation exposure. Our results indicate that prolonged persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…In this study, malignant mesothelioma cases associated with occupational asbestos exposure showed frequent reduction of Fhit protein expression. These observations further support previous suggestions that the FHIT gene alterations may be involved in the development of neoplasms associated with environmental carcinogen exposure [2,6,22,26]. In conclusion, our present data show that absent or markedly reduced Fhit expression was frequent in MM.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, malignant mesothelioma cases associated with occupational asbestos exposure showed frequent reduction of Fhit protein expression. These observations further support previous suggestions that the FHIT gene alterations may be involved in the development of neoplasms associated with environmental carcinogen exposure [2,6,22,26]. In conclusion, our present data show that absent or markedly reduced Fhit expression was frequent in MM.…”
Section: Discussionsupporting
confidence: 94%
“…However, one of the main problems in studying LOH in mitosis is the very low frequency of spontaneous events that can be analyzed in vitro. Nevertheless, LOH may be randomly induced by a variety of physical and chemical agents (Chizhikov et al 2002;Pan et al 2005;Daigaku et al 2006). LOH may also be induced by transposition of DNA-RNA molecules, such as the Moloney murine leukemia virus (Lander and Fan 1997), with considerably higher frequency.…”
Section: Introductionmentioning
confidence: 98%
“…When inhaled, the radionuclides can affect the respiratory system even without the presence of the other coal ash components. Thus, the airborne particles containing radioactive elements inhaled by cleanup workers of the nuclear accident at the Chernobyl nuclear power plant caused bronchial mucosa lesions, in some cases preneoplastic, with an increased susceptibility to the invasion of microorganisms in bronchial mucosa (60,61). Consequently, the combined radioactivity of coal ash at the TVA spill, together with other enriched trace metals such as Ni, Pb, and As, may increase the overall health impact in exposed populations, depending on duration of exposure, and particularly for susceptible groups of the population.…”
Section: Ra/ 226mentioning
confidence: 99%